2011
DOI: 10.1093/jnci/djr030
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive History and Oral Contraceptive Use in Relation to Risk of Triple-Negative Breast Cancer

Abstract: The association between parity and breast cancer risk differs appreciably for ER+ and triple-negative breast cancers. These findings require further confirmation because the biological mechanisms underlying these differences are uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
184
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(207 citation statements)
references
References 33 publications
(41 reference statements)
17
184
2
4
Order By: Relevance
“…12,13,20,46 The HR1 HER22 subtype, which represented an estrogen-derived gene-expression profile, was thought to be more sensitive to hormone exposure. 47 Furthermore, because of endocrinological and environmental changes of the breast before and after pregnancy, the endogenous estrogen exposure before FFTP could be more important than the lifetime endogenous estrogen exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13,20,46 The HR1 HER22 subtype, which represented an estrogen-derived gene-expression profile, was thought to be more sensitive to hormone exposure. 47 Furthermore, because of endocrinological and environmental changes of the breast before and after pregnancy, the endogenous estrogen exposure before FFTP could be more important than the lifetime endogenous estrogen exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been known that nonbreastfeeding increases breast cancer risk, 48 the heterogeneity of associations between breastfeeding and tumor subtypes have been unclear in previous case-case and casecontrol studies. 18,20,46 Because the tumor subtypes of the study population were obtained from two recruiting centers, one limitation of our study is that there might be misclassification bias. However, it was confirmed that the same value of IHC or FISH was used to define the ER, PR and HER2 statuses and that the analyses were adjusted taking into account the recruiting centers in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Neste sentido, os exames frequentemente propostos visam a analisar os locais mais acometidos por metástase a distância no câncer primário da mama, sendo em 51% dos casos o osso, seguido de 17% para o pulmão, 16% para o cérebro e 6% para o fígado 7 . O câncer de mama é uma doença heterogênea, que pode ser dividida em subtipos distintos com base nos padrões de expressão de genes ou marcadores tumorais 8 . Para essa caracterização, realiza-se na avaliação por imuno-histoquímica a pesquisa de receptor de estrógeno (RE), receptor de progesterona (RP) e receptor de fator de crescimento epidermal humano (HER2) 2,8 .…”
Section: Introductionunclassified
“…We know that age at diagnosis and ethnicity are associated with a specific tumor type and tumor behavior, which in turn are influenced by a woman's age at the first pregnancy [10,11]. This indicates that the global incidence of breast cancer changes over time in relation to geography, race and lifestyle changes, suggesting that breast cancer risk is influenced by a multiplicity of still undefined factors.…”
Section: Introductionmentioning
confidence: 99%